A ironia de Geni e o Zepelim: sujeitos, poderes e mundos no tempo da suspensão - Paula, Luciane de [UNESP] (My University, 2010)
The purpose of this article is to analyze the song "Geni e o Zepelim", by Chico Buarque, from the point of view of the social voices present and orchestrated by the narrator. The hypothesis is that the image of the song uncovers the nation´s prejudice by criticizing the hypocrisy conducted by the narrator. In order to do so the song is used as the corpus of analysis, which is taken as a discursive arena where social voices discuss and combat. Therefore, it is possible to analyze the criticism regarding prostitution prejudice and Geni a transvestite inflicted ironically by the narrator’s voice – projected by the authorship in the song. Based on the dialogism present in the subjects voices in the lyrics, considering Bakhtin´s Circle perspectives. The center of analysis is the ironic relationships of power because the subjects position symbolize distinct social power spheres, which by irony are relativized. Therefore, thinking about these relations means reflecting about the construction of a certain speech in time and space, which collaborates with the reconstruction of subjects and social realities.

A proposta desta comunicação é, a partir da canção "Geni e o Zepelim", de Chico Buarque, vista como arena onde se digladiam vozes sociais, analisar a crítica ao preconceito pela prostituição e pela travesti Geni, a "heroína" do discurso. Partir-se-á do dialogismo e da polifonia presentes nas vozes dos sujeitos da letra da canção, abordados a partir da perspectiva do Círculo de Bakhtin. As relações de poder (Bakhtin e Foucault), imbricadas nas relações de gênero, são o centro da análise, a partir do qual será tratada a questão do pertencimento/nãopertencimento de Geni, sua aceitação e recusa, de acordo com os interesses vigentes, por parte dos sujeitos presentes no discurso verbal da canção, que simbolizam esferas de poderes sociais diferentes. Pensar nessas relações significa pensar nas diásporas e nos deslocamentos dos gêneros, bem como isso ocorre na diversidade cultural brasileira. A hipótese é a de que a imagem da canção desvela o preconceito da nação ao criticar a hipocrisia orquestrada por Chico, que rege o coro das vozes sociais, ao mesmo tempo, aclamadoras e apedrejadoras, que apagam Geni, a travesti Maria Madalena da canção.
The irony of Geni and the Zeppelin: Guys, powers and worlds in time of suspension
Keywords: Gender; Geni and Zapelin; Polyphone; Gênero; Geni e o Zapelin; Polifonia